The design student's journey understanding how designers think - Lawson, Bryan (New York Routledge, 2019)
"Being a professional designer is one of the most intellectually rewarding careers. Learning to become a designer can be tremendous fun but it can also be frustrating and at times painful. What you have to do to become a designer is not often clearly laid out and can seem mysterious. Over the past 50 years or so we have discovered a great deal about how designers think. This book relies upon that knowledge but presents it in a way specifically intended to help the student and perhaps the teacher. Bryan Lawson’s classic book How Designers Think has been in print since 1980 and has gone through four editions to keep it up to date. This book can be seen as a companion volume for the design student."--
Design as a set of skills you can learn -- Getting going (actually you've already started) -- From vernacular design to design by drawing -- Drawing in design -- Design schools -- Starting to design -- What's the problem? -- The components of design thinking -- Managing the design process -- What designers know -- The design tutorial -- The crit or design jury or review -- Design conversations -- Design concepts and schemata -- Guiding principles -- Recognising situations, gambits and affordances -- Having more than one idea -- Parallel lines of thought -- Some expert tricks of the trade -- More on conversations with media -- Getting into a design project -- The structure of design problems (1) -- The structure of design problems (2) -- Navigating your design problem -- How are you getting on? -- Moving on.--
Includes bibliographical references and index
Keywords: College environment; Design -- Study and teaching (Higher)